Development of a hearing help-seeking questionnaire based on the theory of planned behavior. (4th May 2019) - Arnold, Michelle; Small, Brent J.; Hyer, Kathryn; Chisolm, Theresa; Frederick, Melissa T.; Silverman, ShienPei C.; Saunders, Gabrielle H.
Abstract: Objective: Our objective was to develop and assess a questionnaire measuring the constructs of the theory of planned behaviour (TPB) regarding older adults' behaviours towards seeking a hearing test. Design: Older adults who failed a hearing screening completed a newly developed Theory of Planned Behavior-Hearing Help Seeking (TPB-HHS) questionnaire. A principal components analysis (PCA) examined the factor structure of the questionnaire, and a reliability analysis determined the internal consistency of the factors. An examination of six-month follow-up data determined whether the questionnaire differentiated between individuals who did and did not seek out a hearing test by comparing their TPB-HHS scores. Study Sample: Participants were 407 adults aged 50 to 89 recruited at community hearing screenings. Results: PCA and reliability analyses resulted in a 4-factor, 18 item questionnaire. Three of four factors demonstrated acceptable internal consistency. The TPB-HHS explained 60.18% of the variance and factors were interpreted to be measuring the constructs of Intentions, Perceived Behavioral Control, Attitudes, and Subjective Norms. Individuals who sought a hearing test scored significantly higher on the Intentions, Perceived Behavioral Control, and Attitudes scales than those who did not. Conclusions: The TPB-HHS provides insight into underlying psychological mechanisms that drive behaviours related to hearing help-seeking in older adults.